Technological Trends In Epidemic Intelligence For Infectious Disease Surveillance: A Systematic Literature Review - Hazeeqah Amny Kamarul Aryffin; Murtadha Arif Bin Sahbudin; Sakinah Ali Pitchay; Azni Hazlizan Ab Halim; Ilfita Sahbudin (USENIX - The Advanced Computing Systems Association, 2025)
Indexed Publication (Tier 2)